202k views
2 votes
Solve for y. 6 x + 2y = z​

User TyrManuZ
by
5.5k points

2 Answers

0 votes
The answer to this question is 7
User Zacqary
by
5.0k points
3 votes

Answer:


y = (z)/(2) -3x

Explanation:

Isolate the variable, y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

PEMDAS =

Parenthesis

Exponents & roots

Multiplication

Division

Addition

Subtraction

& is the order of operation.

First, subtract 6x from both sides:

6x (-6x) + 2y = z (-6x)

2y = z - 6x

Next, divide 2 from both sides:

(2y)/2 = (z - 6x)/2

y = (z - 6x)/2

y = (z/2) - 3x


y = (z)/(2) -3x is your answer.

~

User Kyle Alons
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.